Uso de las Redes Sociales de Internet para mejorar la participación Política de la Juventud Popular Cristiana de Lima Metropolitana - Gómez Torres, Carlos Job (2016)
This thesis entitled "Using social networking sites to enhance the political participation of the People's Metropolitan Lima Christian Youth" aimed to determine whether social networking sites improve political participation From research we can state that 67% of the Popular Christian Youth of Lima politically involved in social networks Facebook, Twitter, YouTube and digital spaces of the Christian People's Party. In addition, the Youth Popular Christian Lima investigated reflects that 100% has a record of account on Facebook, 81% on Twitter, 90% on YouTube and using these social networks with a daily rate of 80%, 70% and 75 % espectively. Also, we note that 58% of the Popular Christian Youth of Lima receives political content in digital spaces of political participation PPC As a recommendation is important to understand the advantages and potentialities of a Plan of Digital Communication, developed by a staff of professionals in Political Science, Communications, Digital Marketing and Advertising in order to measure and achieve effectiveness in the political participation of youth, militants, supporters in the use of social networking sites in the Christian People's Party There is 33% of the People's Metropolitan Lima Christian Youth not participating in politics through social networking sites so an effort is needed to integrate them into the digital connection. For future research should be taken into account as a priority the social network Facebook since it has greater insight into young people and a variety of items for use policy.